How do sphingosine-1-phosphate affect immune cells to resolve inflammation? - Sun, Gehui; Wang, Bin; Wu, Xiaoyu; Cheng, Jiangfeng; Ye, Junming; Wang, Chunli; Zhu, Hongquan; Liu, Xiaofeng (Frontiers in Immunology, 2024)
Inflammation is an important immune response of the body. It is a physiological process of self-repair and defense against pathogens taken up by biological tissues when stimulated by damage factors such as trauma and infection.Inflammation is the main cause of high morbidity and mortality in most diseases and is the physiological basis of the disease. Targeted therapeutic strategies can achieve efficient toxicity clearance at the inflammatory site, reduce complications, and reduce mortality. Sphingosine-1-phosphate (S1P), a lipid signaling molecule, is involved in immune cell transport by binding to S1P receptors (S1PRs). It plays a key role in innate and adaptive immune responses and is closely related to inflammation. In homeostasis, lymphocytes follow an S1P concentration gradient from the tissues into circulation.One widely accepted mechanism is that during the inflammatory immune response, the S1P gradient is altered, and lymphocytes are blocked from entering the circulation and are, therefore, unable to reach the inflammatory site. However, the full mechanism of its involvement in inflammation is not fully understood. This review focuses on bacterial and viral infections, autoimmune diseases, and immunological aspects of the Sphks/S1P/S1PRs signaling pathway, highlighting their role in promoting intradialadaptive immune interactions. How S1P signaling is regulated in inflammation and how S1P shapes immune responses through immune cells are explained in detail. We teased apart the immune cell composition of S1P signaling and the critical role of S1P pathway modulators in the host inflammatory immune system. By understanding the role of S1P in the pathogenesis of inflammatory diseases, we linked the genomic studies of S1Ptargeted drugs in inflammatory diseases to provide a basis for targeted drug development.